Rebalancing Inclusive and Sustainable Growth to Continue Reducing Poverty in Bolivia : Systematic Country Diagnostic Update - World Bank (World Bank, Washington, DC, 2021)
Bolivia made substantial progress in reducing poverty and inequality during the commodity boom, and despite the adverse external context of the past five years, poverty reduction continued, albeit more slowly. Expansionary policies allowed the country to continue growing and reducing poverty until the pandemic but did so at the expense of large macroeconomic imbalances that increased public debt and eroded the buffers. With these challenges exacerbated by the pandemic and limited room to continue fueling domestic demand, igniting other sources of inclusive and sustainable growth calls for addressing both the immediate challenges of the COVID-19 crisis and structural constraints. The three challenges identified five years ago in the first Systematic Country Diagnostic remain, but their urgency has increased.